Kontribusi Lingkungan Kerja Positif Dalam Mendorong Pembentukan Karakter Etis Pegawai Hotel - Christina Anggreani; Selly Ariestina; Nova Syahfitri (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
Employees are not only considered as task executors, but also as representatives of hotel values and image. Character development such as integrity, empathy, and responsibility are top priorities in HR management. Hotel guests today do not only judge from the facilities, but also from the attitudes and behaviour of the staff. Sincere, polite, and empathetic service is a selling point that is influenced by the ethical character of employees. The purpose of this study was to determine the contribution of a positive work environment in encouraging the formation of ethical character of hotel employees. The informants in this study were 4 (four) people, namely employees who work at Grand Mercure Maha Cipta Medan Angkasa. The research method uses a qualitative method. The sampling technique is by using purposive sampling. The data collection method is by using observation, literature study and interview guidelines. Data analysis uses data analysis and theme analysis methods. The results of this study are: A positive work environment will play a role in forming ethical character because it provides a safe and supportive space for employees to develop into ethical individuals and are ready to provide excellent service for employee and guest satisfaction.